2004
DOI: 10.1161/01.hyp.0000139914.52686.74
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and Extracellular Angiotensin II Enhance the L-Type Calcium Current in the Failing Heart

Abstract: Abstract-The influence of intracellular and extracellular angiotensin II (Ang II) on the L-type calcium current of cardiomyocytes isolated from cardiomyopathic hamsters was investigated. The results indicated that Ang II (10 Ϫ8 mmol/L), added to the bath, increased the peak inward calcium current (I Ca ) density by 37Ϯ3.4% (PϽ0.05), an effect that depends on the activation of protein kinase C. Intracellular administration of the same dose of Ang II (10 Ϫ8 mmol/L) also elicited an increase of peak I Ca density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 33 publications
(24 reference statements)
1
37
0
Order By: Relevance
“…Recent studies have shown that intracellular administration of Ang II increases the peak inward calcium current density and decreases the junctional conductance via intracellular AT 1 R in cardiac myocytes (De Mello & Monterrubio, 2004), and intracellular application of an AT 1 R antagonist abolishes the effect of intracellular Ang II. It seems likely that the enhanced sensitivity of IK to hypoxia in CB glomus cells in CHF may be due to elevation of intracellular Ang II binding to intracellular AT 1 R. This notion is evidenced by our observation that intracellular administration of L158,809 (added to the recording pipette solution) blunted the sensitivity of I K to hypoxia in the CB glomus cells from CHF rabbits ).…”
Section: Role Of Ang II On K + Currents In Cb Glomus Cells In Chfmentioning
confidence: 99%
“…Recent studies have shown that intracellular administration of Ang II increases the peak inward calcium current density and decreases the junctional conductance via intracellular AT 1 R in cardiac myocytes (De Mello & Monterrubio, 2004), and intracellular application of an AT 1 R antagonist abolishes the effect of intracellular Ang II. It seems likely that the enhanced sensitivity of IK to hypoxia in CB glomus cells in CHF may be due to elevation of intracellular Ang II binding to intracellular AT 1 R. This notion is evidenced by our observation that intracellular administration of L158,809 (added to the recording pipette solution) blunted the sensitivity of I K to hypoxia in the CB glomus cells from CHF rabbits ).…”
Section: Role Of Ang II On K + Currents In Cb Glomus Cells In Chfmentioning
confidence: 99%
“…Intracellular angiotensin II reduced the L-type Ca 2+ current in rat ventricular cells, whereas the opposite was observed in hamsters (18). Angiotensin II increases the L-type Ca 2+ current through protein kinase C-dependent pathways (19). The T-type Ca 2+ current is increased by angiotensin II stimulation (20).…”
Section: Discussionmentioning
confidence: 97%
“…Virtually identical increases in HVA current were observed in ventricular myocytes isolated from rats in heart failure. 16 In the absence of a change in membrane permeability, possible explanations for the increased HVA current include alterations in the number of VGCCs and/or modulation of the channel by intracellular signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%